Expression of COX-1 and COX-2 in the endometrium of cyclic, pregnant and in a model of pseudopregnant rats and their regulation by sex steroids - St-Louis Isabelle; Singh Mohan; Brasseur Kevin; Leblanc Valérie; Parent Sophie; Asselin Eric (BMC, 2010)
Abstract Background Cyclooxygenases (COXs) are the rate limiting enzymes in the process of prostaglandins (PGs) synthesis, which are critical regulators of a number of reproductive processes, including ovulation, implantation, decidualization and parturition. The aim of the present study was to investigate the expression and regulation of COX-1 and COX-2 and levels of prostaglandins during rat pregnancy, in a model of pseudopregnancy and estrous cycle. Methods Uteri were collected from the cyclic rats on each day of estrous cycle, after every two days for pregnant (days 2 to 22) and pseudopregnant rats (days 1 to 9). In vitro primary endometrial stromal cells were cultured in the presence of steroid hormones and their respective inhibitors for the possible modulation of COX-1 and COX-2. Endometrial protein extracts were used for western blot analysis and tissue sections were prepared for protein localization using immunofluorescence. Measurements of PGF2alpha and PGE2 metabolites in serum were performed by enzyme immunoassay (EIA). Results COX-1 expression was found to be elevated during implantation and parturition, however, the levels of COX-1 decreased during decidualization periods. COX-2 was detected during early pregnancy from day 2 to 5, increased during decidual regression, and was also expressed at the time of parturition. COX-2 protein expression was found to be increased at estrus phase in cyclic rats. Both enzymes were found to be modulated in the endometrium of pseudopregnant rats, suggesting that they are regulated by 17beta-estradiol and progesterone. A significant increase in PGE2 metabolite levels was observed on day 10, 12 and 14 of pregnancy. However, an increase in PGF2alpha metabolite levels was observed only on day 14. The concentration of both these metabolites changed during pseudopregnancy and maximum levels were observed at day 7. Significant increase in PGE2 metabolite was observed at proestrus phase, on the other hand, PGF2alpha metabolite was significantly increased at proestrus and metestrus phase. COX-2 protein was regulated by 17beta-estradiol in cultured endometrial stromal cells which was blocked in the presence of ICI-182,780. Conclusions Taken together, these results suggest that COX-1 and COX-2 could be differentially regulated by steroid hormones and might be the key factors involved in embryo implantation, decidualization, decidua basalis regression and parturition in rats.